2004
DOI: 10.1099/vir.0.80241-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural simian foamy virus infection in wild-caught gorillas, mandrills and drills from Cameroon and Gabon

Abstract: A survey for the presence of simian foamy retroviruses (SFVs) was performed in 44 wild-caught apes and monkeys, including 27 gorillas, 11 mandrills and six drills, originating from south Cameroon or Gabon. Combined serological and/or nested-PCR assays indicated SFV infection among five Gorilla gorilla gorilla, seven Mandrillus sphinx and two Mandrillus leucophaeus. Sequences of a 425 bp fragment of the integrase gene were obtained for 11 animals. Phylogenetic studies indicated that strains from gorillas, mandr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 28 publications
(30 reference statements)
3
48
0
2
Order By: Relevance
“…A significant diversity is observed among FVs VOL. 80, 2006 FOAMY VIRUS RESTRICTION BY APOBEC CYTIDINE DEAMINASES 611 from different simian species, suggesting that cross-species infection was associated with adaptative changes (7,15). However, within each monkey species, viral persistence is associated with strong genetic stability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant diversity is observed among FVs VOL. 80, 2006 FOAMY VIRUS RESTRICTION BY APOBEC CYTIDINE DEAMINASES 611 from different simian species, suggesting that cross-species infection was associated with adaptative changes (7,15). However, within each monkey species, viral persistence is associated with strong genetic stability.…”
Section: Discussionmentioning
confidence: 99%
“…1D). We also studied the susceptibility of primary FV strains, isolated from naturally infected macaques (7). To study the effect of hA3G, we compared viral spread in control HeLa cells and in HeLa cells stably expressing hA3G (HeLa-hA3G cells) (27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the captive animals examined have been macaques and baboons (3,7). Recently, it was shown that colonies of NHPs living in the wild, including various species of monkeys and apes in Africa (mandrills, gorillas, chimpanzees) and Asia (subspecies of macaques), are also infected with simian foamy virus (SFV) (6,13,17). The oral mucosa has been shown to be the main site of SFV replication in vivo, and saliva appears to be the principal reservoir of SFV (20).…”
mentioning
confidence: 99%